The Influence of Cooperative Script on Students’ Reading Comprehension in the Tenth Grade at SMA Negeri 7 Bandar lampung during the Academic Year 2023/2024 - Rowi, Alifia Cahya; Febriyantina Istiara; Eva Nurchurifiani (Lentera: Jurnal Ilmiah Kependidikan, 2024)
Cooperative script is one strategy that can be used in reading comprehension. This strategy can help students comprehend the main idea, specific information, inferences, references, and vocabulary. The aim of the research to know the influence of using cooperative scripts on students' reading comprehension. The method in this research is experimental method in the quasi-experimental research design. In taking research samples, the writer used cluster random sampling. In using cluster random sampling, the writer take random samples from existing classes or populations to be used as research samples. The population in this research were students in the second semester of the tenth grade at SMA Negeri 7 Bandar Lampung during the academic year 2023/2024. The samples for this research were classes X.1 it consist of 35 and X.5 it consist of 34. In collecting data about students' reading comprehension, the writer used reading test. Based on the data calculation, the average score of experimental class was 77.9 and the average score of control class was 73.1. It means that the average score of experimental class is higher than control class. Based on calculating t-test was obtained 2.77 than t-table at signifinance level of 0.05 is 1.99 and 0.01 is 2.56. T-test > t-table it means t-test higher than t-table. So, there is an influence of cooperative script on students' reading comprehension in the tenth grade at SMA Negeri 7 Bandar Lampung.